Arrhenius model for styrene monomer migration from single-use polystyrene cup - Mat-Shayuti, M.S. (Elsevier Ltd, 2020)
Harmful chemicals leaching into beverage contained in polystyrene (PS) cup is a concern for consumers, therefore this paper seeks to investigate the pattern of styrene monomers migration with respect to temperature. PS cups containing liquid stimulants (distilled water & cooking oil) were subjected to temperatures of 25-100 Â°C. Gas chromatography-mass spectrometry (GC-MS) showed no hint of styrene in distilled water but detected styrene traces in the cooking oil to be proportional with temperature. The migration rate jumped above 75 Â°C, suggesting a threshold point for enhanced styrene absorption. This could be attributed to the compromised structural integrity of the cup and greater styrene solubility in the cooking oil above 75 Â°C. The activation energy required for styrene migration from the PS cup computed through Arrhenius equation was 12.117 kJ/mol. Despite the finding, the highest recorded styrene content which was 1.1158 Ã 10-4wt at 100 Â°C still fell below the maximum allowable limit of 0.5 wt set by the U.S. Food and Drug Administration (FDA). Â© 2020 Elsevier Ltd. All rights reserved.